Clinical features, pathogens, and prognosis of immunocompromised host pneumonia in patients with malignancies - Fang, Xiang-Zhi; Liu, Zi-Han; Duan, Li-Min; Yao, Lu; Xu, Ji- Qian; Yang, Xiao-Bo; Ren, Le-Hao; Jiang, Yong-Xiang; Sun, Sheng-Wen; Shang, You; Yuan, Yin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCancer patients face elevated risks of severe pulmonary infections due to malignancy-related immunosuppression and anti-neoplastic therapy. Comprehensive data on the etiology and prognostic factors remain limited.MethodsThis prospective cohort study enrolled 115 patients with malignancies and immunocompromised host pneumonia (ICHP) from July 2023 to July 2024. Pathogens were identified using clinical metagenomics of bronchoalveolar lavage fluid (BALF), supported by CT imaging and clinical evaluation.ResultsPathogens were detected in 92 patients (80.0%), with 158 potential pathogens detected. Etiologic diagnoses were established by BALF mNGS alone in 68 (73.9%), by combined mNGS plus standard microbiologic testing (SMT) in 24 (26.1%), and by SMT alone in 1 (1.1%). Pneumocystis jirovecii (32, 20.3%), SARS-CoV-2 (14, 8.9%), Aspergillus fumigatus (13, 8.2%), Klebsiella pneumoniae (12, 7.6%) and Haemophilus influenzae (10, 6.3%) were the five most common pathogens. Coinfections occurred in 36.5% of all enrolled patients. Death at 28 days, ICU admission, Death at ICU was more frequent among patients with polymicrobial infections than single pathogen infection, though this difference was not statistically significant. Use rate of vasoactive drugs was significantly higher in patients with coinfection than in patients with single-pathogen infection (39.1% vs. 16.0%). invasive mechanical ventilation (IMV) (OR = 22.86, p=0.047), vasopressor use (OR = 72.69, p=0.039), and higher Acute Physiology and Chronic Health Evaluation II (APACHE II) scores (OR = 1.46, p=0.016) were associated with increased 28-day all-cause mortality.ConclusionPatients with malignancies and evaluated for pulmonary infection were found to have unique microbiological profiles detected by BAL metagenomic sequencing. Co-detection of potential pathogens was high, and associated with high 28-day all-cause mortality.